Jenis Air Rendaman pada Singkong (Manihot esculenta) Terhadap Penurunan Kadar Asam Sianida (HCN) - Fadlilah, Hidayatul; Narwati, Narwati; Rachmaniyah, Rachmaniyah; Marlik, Marlik; Mirasa, Yudied Agung (POLTEKKES KEMENKES MANADO, 2022)
Cassava naturally contains cyanogenic glycosides, which have the potential to become hydrogen cyanide (HCN) toxic. Cassava can be safer to be consumed if it is conducted pre-processing and processing. One of example of pre-processing is soaking. The objective of this research was to comprehend the effect of soaking water type in cassava on the hydrogen cyanide (HCN) reduction level. This research was a pre-experimental research with After Only Design. The objects of research was cassavas with a total of 18 samples. The types of soaking water was in the form of 10% of table salt solution concentration, 10% calcium hydroxide solution concentration, and PDAM water (control) with an initial temperature of 55ºC. The soaking time was conducted for 120 minutes. The method of hydrogen cyanide examination level using a titrimetric method. The data that had obtained was then analyzed using an Anova test. The result of while cassavas’ HCN level after soaking with table salt solution was 63 mg/kg, calcium hydroxide solution was 70 mg/kg, and PDAM water was 175 mg/kg. The Anova test indicated that there was a difference in hydrogen cyanide level value from three types of soaking water in cassava (p < 0.05). The conclusion of this research is that there is an effect of soaking water type on hydrogen cyanide (HCN) level value which is contained in cassava